1997
DOI: 10.1084/jem.186.4.489
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Inhibits Bone Resorption by Directly Inducing Apoptosis of the Bone-resorbing Osteoclasts

Abstract: Estrogen deficiency causes bone loss, which can be prevented by estrogen replacement therapy. Using a recently developed technique for isolation of highly purified mammalian osteoclasts, we showed that 17 β-estradiol (E2) was able to directly inhibit osteoclastic bone resorption. At concentrations effective for inhibiting bone resorption, E2 also directly induced osteoclast apoptosis in a dose- and time-dependent manner. ICI164,384 and tamoxifen, as pure and partial antagonists, respectively, completely or par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
268
2
12

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 442 publications
(297 citation statements)
references
References 38 publications
15
268
2
12
Order By: Relevance
“…Evaluation of apoptosis was carried out as previously described (9). After a 48 hour treatment, cells were fixed in 3.7 % formaldehyde solution for 5 min and stained with 0.2 mM Hoechst 33258 (SIGMA, France) for 10 min.…”
Section: -5 Osteoclast Apoptosis Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of apoptosis was carried out as previously described (9). After a 48 hour treatment, cells were fixed in 3.7 % formaldehyde solution for 5 min and stained with 0.2 mM Hoechst 33258 (SIGMA, France) for 10 min.…”
Section: -5 Osteoclast Apoptosis Assaymentioning
confidence: 99%
“…Most of them have shown the capacity to reduce bone resorption e.g. estrogens (9), bisphosphonates (10), calcitonin (11), selective oestrogen receptor modulators (12). However, to date, none of these agents has been able to completely abolish the development of new bone fractures.…”
Section: -Introductionmentioning
confidence: 99%
“…28 This groundbreaking observation led the way for the exploration of the mechanism of how estrogen caused apoptosis. Kousteni, et al, suggested that apoptosis in osteoclasts was induced via a non-genomic pathway 3 .…”
Section: Is Apoptosis In Osteoclasts Induced By a Non-genomic Pathway?mentioning
confidence: 99%
“…Estrogens, in particular 17-␤ estradiol (E 2 ), are well-characterized mitogens for mammary tissues and epithelial cells of the female reproductive tract. Whereas estrogens exert antiapoptotic influence in neurons (Zhang et al, 2001), epithelial cells of the female reproductive tract (Leung and Wang, 1999;Choi et al, 2001), immune system, blood cells, and endothelial cells (Bynoe et al, 2000;Haynes et al, 2000), they also have significant apoptotic effects on certain classes of bone-derived cells (Hughes et al, 1996;Kameda et al, 1997) and some immune system cells (Zajchowski and Hoffman-Goetz, 2000;Okasha et al, 2001).…”
Section: Introductionmentioning
confidence: 99%